2018
DOI: 10.1002/hbm.24347
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional cerebral bases of diminished inhibitory control during healthy aging

Abstract: Inhibitory control or the ability to refrain from incorrect responses is a critical executive function known to diminish during aging. Imaging studies have elucidated cerebral changes that may underlie the age-related deficits. However, it remains unclear whether the structural and functional changes occur in the same brain regions and whether reduced gray matter volumes (GMV) mediate decreased activation during inhibition. Here, in a sample of 149 participants, we addressed the issues using structural and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 80 publications
5
47
0
Order By: Relevance
“…Even though it was under debate whether inhibition and switching are age-related abilities, according to our study, both abilities seem to change during lifespan. Our study comes to an agreement with others that show a decrease in activation of inhibitory control [70] and switching as well [71]. Therefore, ICT/RST-S1&S2 and ICT/RST-FS in consistency with the age-relation literature, can differentiate the SCD people from the HYA and HMaA.…”
Section: Ict/rst-s1ands2 and Ict/rst-fs Differential Abilitysupporting
confidence: 92%
“…Even though it was under debate whether inhibition and switching are age-related abilities, according to our study, both abilities seem to change during lifespan. Our study comes to an agreement with others that show a decrease in activation of inhibitory control [70] and switching as well [71]. Therefore, ICT/RST-S1&S2 and ICT/RST-FS in consistency with the age-relation literature, can differentiate the SCD people from the HYA and HMaA.…”
Section: Ict/rst-s1ands2 and Ict/rst-fs Differential Abilitysupporting
confidence: 92%
“…Under pathological conditions including atrophy, lower GMV is commonly assumed to lead to decreased function, because it is mostly found in functionally impaired subjects, i.e. in patients or in the aging brain [69]. A positive association of subclinical symptoms with GMV as in some of the mentioned studies appears less intuitive.…”
Section: Methodical Considerationsmentioning
confidence: 99%
“…For example, in behavioral paradigms to examine conflict monitoring and resolution, such as the go/no-go, flanker, Stroop, and stop signal task (SST), participants not only adjust behavior according to the stimuli but also anticipate behavioral adjustment according to what they have learned from the tasks. We previously showed that the efficiency of reactive control in the SST diminished with age, as reflected by longer stop signal reaction time (SSRT), and was associated with reduced activations in the medial prefrontal cortex and right inferior frontal gyrus pars opercularis/anterior insula in older adults (Hu et al 2018). The current work aimed to investigate age-related changes in proactive control and whether these changes may influence reactive control in the SST.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we investiageted the neural mechanisms relating proactive to reactive control and specifically how regional activations to conflict anticipation may influence the SSRT. As age was associated with longer SSRT (Hu et al 2012; Hu et al 2018) and cerebral responses to proactive control have been related to SSRT (Hu et al 2016), we hypothesized that regional activations and FC in support of proactive control did not benefit reactive response inhibition, as indexed by SSRT, during aging.…”
Section: Introductionmentioning
confidence: 99%